Avaliação de parâmetros biofísicos, derivados de dados satelitários, na área de influência do reservatório da UHE Luís Eduardo Magalhães - TO - Pires, Érika Gonçalves (2017)
The changes in land-cover and land-use are among the main causes of a series of environmental, social, and economic impacts. In particular, the formation of artificial reservoirs, due to the construction of hydroelectric plants (HPP), has been the subject of scientific studies in the country, mainly due to the changes they cause to the environment. Specifically, the construction of the Luís Eduardo Magalhães HPP in 2001 (along the Tocantins River), in a context of large-scale constructions in the state of Tocantins, resulted in a large flooded area (~ 630 km²), significant changes in the landscape, and relocation of rural and urban populations. In this sense, this work aimed to evaluate and quantify, through various satellite datasets and land-cover and land-use mapping of the area under the influence of the reservoir of the Luís Eduardo Magalhães HPP (in the period before and after its implementation), changes in the landscape and associated biophysical parameters. At the landscape scale, the following surface parameters, derived from Terra-MODIS images, were evaluated seasonally: temperature, vegetation index, evapotranspiration, and albedo. The analysis of these data, in the spatial - temporal domains, involved three experimental models: a) considering the area of influence of the reservoir as a whole (equidistance of 30 km); b) analysis considering the equidistance or proximity to the reservoir (through buffers, latitudinal transects, and areas of interest); c) comparisons between the MODIS sensor results and the biophysical parameters obtained from Landsat images (transformed by the SEBAL algorithm). The results of our research show the potential of using remote sensing images in the study of variations of biophysical parameters. The implementation of the Luís Eduardo Magalhães HPP reservoir boosted the occupation of areas around it, especially: the São João irrigation project (irrigation from lake water), the increase in real estate speculation through the creation of new land subdivisions and closed condominiums with direct access to the lake, occupation of other areas due to the relocation of families (as in the case of the district of Luzimangues-Porto Nacional), and the creation of condominiums near the reservoir. Between 2000 and 2014, there was a 111% decrease in the Cerrado native vegetation (forest formations, grassland formations, open and dense Cerrado Strict Sensu physiognomies) and an increase of 66% in urban areas and 947% in the agricultural areas. It was also observed that almost half of the entire study area (42%) suffered some kind of alteration in the land cover. The changes observed in the local biophysical parameters were a direct result of the reservoir implantation and the State's occupation and development policies (such as soybean financing), which influenced the spatial configuration of the various land-cover classes and existing land use in the study area. As a result, a number of negative environmental / climatic impacts are already perceived in the area. Therefore, it is suggested to implement public policies regarding the systematic monitoring of biophysical parameters in the area, with a view to minimizing and mitigating more severe long-term environmental impacts.